99mTc‐MIP‐1404‐SPECT/CT for the detection of PSMA‐positive lesions in 225 patients with biochemical recurrence of prostate cancer. Issue 1 (6th November 2017) - Schmidkonz, Christian; Hollweg, Claudia; Beck, Michael; Reinfelder, Julia; Goetz, Theresa I.; Sanders, James C.; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Cavallaro, Alexander; Uder, Michael; Wullich, Bernd; et al.
Abstract : Background: 99m Tc‐MIP‐1404 (Progenics Pharmaceuticals, Inc., New York, NY) is a novel, SPECT‐compatible 99m Tc‐labeled PSMA inhibitor for the detection of prostate cancer. We present results of its clinical use in a cohort of 225 men with histologically confirmed prostate cancer referred for workup of biochemical relapse. Methods: From April 2013 to April 2017, 99m Tc‐MIP1404‐scintigraphy was performed in 225 patients for workup of PSA biochemical relapse of prostate cancer. Whole‐body planar and SPECT/CT images of the lower abdomen and thorax were obtained 3‐4 h p.i. of 710 ± 64 MBq 99m Tc‐MIP‐1404. Images were visually analyzed for presence and location of abnormal uptake. In addition, quantitative analysis of the SPECT/CT data was carried out on a subset of 125 patients. Follow‐up reports of subsequent therapeutic interventions were available for 59% (139) of all patients. Results: Tracer‐positive lesions were detected in 77% (174/225) of all patients. Detections occurred at the area of local recurrence in the prostate in 25% of patients (or a total of 56), with metastases in lymph nodes in 47% (105), bone in 27% (60), lung in 5% (12), and other locations in 2% (4) of patients. Detection rates were 90% at PSA levels ≥2 ng/mL and 54% below that threshold. Lesional SUVmax values were, on average, 32.2 ± 29.6 (0.8–142.2), and tumor‐to‐normal ratios 146.6 ± 160.5 (1.9–1482.4). The PSA level correlated significantly with total uptake of MIP‐1404 in tumors ( P  < 0.001). Furthermore, total tumor uptake was significantly higher in patients with Gleason scores ≥8 compared to those with Gleason scores ≤7 ( P  < 0.05). In patients with androgen deprivation therapy, the detection rate was significantly higher compared to patients without androgen deprivation therapy (86% vs 71%, P  < 0.001). Based on 99m Tc‐MIP‐1404‐imaging and other information, an interdisciplinary tumor board review recommended changes to treatment plans in 74% (104/139) of those patients for whom the necessary documentation was available. Conclusion: SPECT/CT with 99m Tc‐labeled MIP‐1404 has a high probability in detecting PSMA‐positive lesions in patients with elevated PSA. Statistical analysis disclosed significant relationship between quantitative 99m Tc‐MIP‐1404 uptake, PSA level, and Gleason score.